PENERAPAN MODEL EXPERIENTIAL LEARNING BERBANTUAN MEDIA DADU BERGAMBAR UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATEMATIKA PADA MATERI PENYAJIAN DATA - sholihah, muna khansa; sanoto, herry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Fourth-grade students aged 7–11 are in the concrete operational stage, making it easier for them to understand mathematical concepts through real-life experiences. However, the teaching methods applied have not sufficiently incorporated hands-on activities, resulting in low interest and poor learning outcomes. This study aimed to implement the experiential learning model using illustrated dice media to improve cognitive learning outcomes at SDN Pulutan 02. This Classroom Action Research adopted the Initial Reflection model by Rustiyarso and Tri Wijaya, involving 11 students as subjects. Data were collected through tests and interviews. The results showed an increase in the average score from 69 in Cycle I to 79 in Cycle II, and classical mastery from 65% to 82%. Improvements were observed in the aspects of understanding, application, analysis, and creation, although evaluation still required guidance. The process also enhanced students’ engagement, curiosity, and collaboration, and helped them understand data presentation in real-life contexts. This model is recommended for use in other learning contexts, accompanied by reflection activities to strengthen evaluative skills and connect material to students’ everyday experiences.